PENGARUH KOMPENSASI, GAYA KEPEMIMPINAN, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA KOPERASI UNIT DESA PAKIS KABUPATEN MALANG - Dharma Yudha; Abdul Qodir Djaelani; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to examine and analyze the influence of leadership style, leadership style and work motivation on cooperative Pakis village units both partially and jointly. Population and sample are all administrators totaling 42 people. Data collection through questionnaires and interviews. Data analysis in this study using SPSS version 17. The sampling technique using questionnaire deployment methods and data testing techniques used in this study include validity test, reliability test, normality test, classic assumption, multiple linear regression analysis, and testing the research hypothesis .The results of the analysis show that partially compensation has a significant effect on employee performance, while leadership style and work motivation do not affect the performance of employees of the fern village unit cooperative. Together, it shows that compensation, leadership style and work motivation have a significant effect on employee performance Leadership in the fern village unit cooperative.Keywords: Compensation, Leadership Style and Work Motivation on Employee Performance